Evapotranspiration changes of reference Crop during the growth stages of apple tree in Urmia and Semirom cities - minoo ahmadyan; Bahroz sobhani; sobhani@uma.ac.ir Jahanbakhsh Asl (تحقیقات کاربردی علوم جغرافیایی)
The evapotranspiration of the reference Crop is of particular importance due to the changes in climate parameters of temperature, sunlight, humidity and wind speed in combination. the purpose of this study is to investigate the effects of climate change on evapotranspiration of apple during the growing season.For this purpose, the ECMWF database has been used for observation data of Semirom and Urmia stations during 20-year period (1996-2001).To check this quantity in the next 20 years, the daily  Downscaling dynamic data of the CORDEX project with a precision of 44% * 44% for the output of the ICHEC-EC-EARTH model under the two lines of 4.5 and 8.5 (RCP) was used for the period (2017-2037). In order to reduce the errors in the model estimates, the post-processing action of the estimated events was fulfilled. Then, minimum temperature data, maximum temperature, relative humidity, wind speed and radiation, potential evapotranspiration have been calculated using Penman- Monteith FAO method, which is more accurate than other models, and using the non-parametric Man-Kendall test and the Sen’s Slope estimator nonparametric Method in the confidence range, 95% evapotranspiration was determined. The results showed that evapotranspiration in both stations is increasing during the growing season. The ETo increase in the growth season of the apple tree stations was predicted from the base period for the trajectory of 4.5 and 8.5 for the Semirom 4.14.7 and 7.99.7, respectively, and for Orumiye Station, 26.5 and 11.8, respectively